"On the Border of Old Age": An Entangled History of Eldercare in East Germany. Issue 2 (June 2020) - Chappel, James
ABSTRACT: Historical research has turned in the last years more intensively toward entangled and transnational histories of biopolitics, the family, and the welfare state, but without renewed interest in aging and pension policy, a sphere of human experience that is often interrogated in parochial terms, if at all. An analysis of the culture and policies of old age in East Germany in the 1950s and 1960s shows the importance of a transnational history of this subject. The GDR, the Communist state with the greatest proportion of elderly citizens, needed to create a socialist model of aging. Neither the Communist tradition in Weimar Germany, nor the experience of the other states in the Communist bloc provided substantial guidance. East Germans looked instead for inspiration to West Germany, which was itself engaged in a debate about aging and pension policy. By grappling with the Western experience, including its perceived and real limitations, the GDR in the Ulbricht developed a vision of what it meant to age as a socialist.